Nivel de efectividad de la funcionalidad familiar en mujeres que han experimentado cáncer de mama (2020)
Introduction: Cancer is a disease that generates alterations in people's bodies, but it could also have the particularity of affecting the functionality of families. Objective: To determine the level of effectiveness of family functionality in 25 women who have experienced breast cancer, belonging to a support network in the city of Montería, Colombia. Method: Descriptive-cross-sectional study with a quantitative approach. Data collection was carried out through the application of a sociodemographic survey designed by the researchers and the “scale of evaluation of the effectiveness of family functionality” in its free version in Spanish by Marie Luise Friedemann, which facilitated the evaluation of 20 items that they make up dimensions and goals that together make up the family functionality. Results: Participating women are aged between 33 and 84 years, with 28% being between the ages of 44 and 53; they live in the low-low stratum (52%), married (36%), living with partners and children (44%), technical education level (40%) and spirituality (84%) is the most preferred support network. The evaluation of the dimensions of the family system showed high levels of system maintenance (84%) and changes in the system (48%), but individuation (60%) and coherence (48%) reported intermediate levels; The goals, on the other hand, reflected intermediate levels of growth (60%), spirituality (64%) and the goal of stability (72%) and control (64%) was located at a high level Conclusions: 80% of the participants have a low level of effectiveness of family functionality, followed by 20% whose level is intermediate, results that indicate the need to work on the dimensions of individuation and coherence and on the goals of growth and spirituality to achieve effectiveness in the family system.